APLIKASI E-BOOK BERBASIS ANDROID UNTUK MENDUKUNG PEMBELAJARAN INTERAKTIF DI SMK SENTOSA BHAKTI - Pujianto, Defi (Universitas Mahakarya Asia, 2024)
Abstract – This Android-based e-book application was developed as an innovative solution to address the limitations of conventional learning methods, which often face challenges related to the availability and accessibility of physical textbooks. This phenomenon reflects a paradigm shift in the education sector, emphasizing the integration of technology to enhance the effectiveness and accessibility of learning processes. With the rising popularity of e-books, new opportunities have emerged to support educational innovation, particularly at SMK Sentosa Bhakti. This research employs a qualitative descriptive method with primary steps including interviews, observations, and reference studies. The research process involves problem identification, goal setting, literature review, application design, and development. Through the implementation of this application, it is expected to have a positive impact on improving the quality of learning at SMK Sentosa Bhakti, facilitating material management by administrators, and enriching students' learning experiences by providing easier and more interactive access to educational resources.